2020
DOI: 10.1088/1361-6463/aba01e
|View full text |Cite
|
Sign up to set email alerts
|

A poly-diagnostic study of bipolar high-power magnetron sputtering: role of electrical parameters

Abstract: Ion acceleration in a bipolar high-power impulse magnetron sputtering discharge working with Ar gas and using a Ti cathode has been investigated. The multiple discharge diagnostic approaches have been implemented, including the target and substrate current probe measurements, mass spectrometry and laser-induced fluorescence. In particular, the current waveforms were analysed in detail, showing the particularities of the current evolution during the negative (plasma) and positive voltage pulses. It is shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…In the HiPIMS and BPH cases, the samples were called HIP26A, BPH26A, HIP70A, and BPH70A, with the numbers corresponding to peak current values during the negative pulse, I P − = 26 A and I P − = 70 A, respectively. For clarity, this notation was utilized in the rest of the paper while further information about the definition of BPH parameters can be found elsewhere [30]. In the BPH case, the delay between the negative and the positive pulses, τ ± , was fixed at 10 µs and the positive pulse width, τ + , was fixed at 250 µs.…”
Section: Hipims and Bph Plasma Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…In the HiPIMS and BPH cases, the samples were called HIP26A, BPH26A, HIP70A, and BPH70A, with the numbers corresponding to peak current values during the negative pulse, I P − = 26 A and I P − = 70 A, respectively. For clarity, this notation was utilized in the rest of the paper while further information about the definition of BPH parameters can be found elsewhere [30]. In the BPH case, the delay between the negative and the positive pulses, τ ± , was fixed at 10 µs and the positive pulse width, τ + , was fixed at 250 µs.…”
Section: Hipims and Bph Plasma Sourcementioning
confidence: 99%
“…In the BPH case, the negative (plasma) pulse, necessary for sputtering and ionizing the metal atoms, is followed by a positive voltage pulse to accelerate the positive ions towards the substrate surface [26]. Plasma diagnostics of BPH discharges [26][27][28][29][30][31][32] as well as the analysis of film properties [33] have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A bi-polar HIPIMS, 14,[30][31][32][33][34] applying a reverse positive pulse at the end of the negative pulse during the HIPIMS discharge, is gaining a great deal of interest. However, there are few reports regarding the relationship between the reverse positive voltage pulse parameter and the behavior of HIPIMS plasma.…”
Section: Resultsmentioning
confidence: 99%
“…2.16. Other studies also observed a shift of the ion energies with an increase in Urev [25,117,120,124,125], though some works exhibit accelerated peaks that are a few tens of eV less than Urev [27,28,126]. The dominant thermal peak is also observed to decrease with the application of the positive pulse since most of these slow-moving ions get accelerated by the potential drop.…”
Section: Iedf In Bipolar Hipimsmentioning
confidence: 93%
“…These factors are dependent on parameters such as the current density and on the pulsing procedure applied. Michiels et al [120] varied the peak current density of the main HiPIMS pulse, which resulted in an increase of the substrate peak current detected during the positive pulse indicating an increase in the amount of ions arriving at the substrate. The effect of changing the length of the negative pulse, , and the positive pulse, , is investigated in Paper III.…”
Section: Bipolar Hipimsmentioning
confidence: 99%